Assessment and Evaluation of a School-based Values Formation Program - Olaya, Christopher (Journal of Interdisciplinary Perspectives, 2024)
This study addresses the observed decline in values and moral character among Filipino students, as evidenced by their communication and interactions with peers, teachers, and others. To counter this trend, a school-based values formation program was implemented. The research aimed to evaluate the acceptability of the program. Using descriptive narrative and inferential statistics, the study found that the program has a profound and positive impact, effectively instilling positive values and character traits in students. The results indicated no significant difference in acceptability levels between parents and teachers, with both groups highly endorsing the project. These findings provide a strong case for schools to adopt the program to promote positive values and character traits among students. The study recommends implementing the program in all Pililla Sub-Office and Division of Rizal elementary schools, offering a practical solution to the observed decline in values. Furthermore, it encourages teachers to develop similar programs with varying scopes of values and character integration, providing a flexible approach to values formation. Establishing a regular values formation program as part of the annual school action plan is also advised, ensuring the sustainability of the program. Finally, the study recommends enhancing the existing program for greater effectiveness and conducting parallel studies considering additional variables, suggesting avenues for further research and program improvement.